AN UNDERSTANDING THE SOCIAL NETWORKING OF THE PEPPER FARMERS IN BANGKA SELATAN, INDONESIA - Eddy Jajang Jaya Atmaja; Novyandra Ilham Bahtera; Laila Hayati (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2022)
Currently, the local government has put extra efforts on the pepper as the eminent commodity in Bangka Belitung Islands Province. The concern of the government is emphasized on how to uplift the welfare of the farmer. However, the efforts have not met the expectancy as the society remains at the unfavourable situation. The study aims to understand the social networking among the farmers and the stakeholders as the endeavour to scrutinize the communication pattern amongst them. The data collection was conducted on September 2021. The quantitative data using purposive sampling was employed as the data collection technique. The Ucinet software was applied as the analytic technology by showing the sociogram. The study found how the close relationship amongst the actors affect the farming activity. The finding was expected to be used by policy maker to determine the best extension program in the future so that the farmers can improve their living condition.